Evaluation of Different Restoration Combinations Used in the Reattachment of Fractured Teeth: A Finite Element Analysis - Nagihan Guven; Ozgur Topuz; İhsan Yikilgan (Applied Bionics and Biomechanics)
Objective. The purpose of this study was to test different restoration combinations used for constructing fractured endodontically treated incisors by reattaching their fractured fragments. Methods. Seven types of 3-D FEM mathematical root canal-filled models were generated, simulating cases of (OB) reattaching fractured fragments; (CrPL) reattaching fractured fragments + ceramic palatinal laminate; (CmPL) reattaching fractured fragments + composite palatinal laminate; (CM) reattaching fractured fragments + coronal 1/3 of the root was filled using core material; (BP) reattaching fractured fragments + glass fiber post; (CP) composite resin restoration + glass fiber post; and (OC) composite resin restoration. A 100-N static oblique force was applied to the simulated teeth with 135° on the node at 2 mm above the cingulum to analyze the stress distribution at the tooth. Results. For enamel tissue, the highest stress values were observed in model BP, and the lowest stress values were observed in model CmPL. For dentine tissue, the highest stress concentrations were observed around the fracture line for all models. Conclusions. Reattachment of fractured fragments by bonding may be preferred as a restoration option for endodontically treated incisors; also, palatinal laminate decreases the stress values at tooth tissues, especially at the enamel and the fracture line.